Pri micropeptide functions as a cell-intrinsic timer controlling the transient phase of cell fate induction - Sonoko Mizuno; Tadashi Uemura; Takefumi Kondo (Proceedings of the National Academy of Sciences, 2026)
During development, cells sequentially acquire specific fates through temporally ordered regulatory systems. To ensure the harmonious progression, each system must be activated and subsequently inactivated at the appropriate time. In this study, we show that the duration of fate induction is controlled by the transient expression of polished rice ( pri ), a gene encoding micropeptides, during Drosophila tracheal development. pri is transiently expressed in prospective tracheal placodes and precedes the expression of trachealess ( trh ), a master transcription factor that initiates tracheal fate. pri induces the expression of trh through promoting the disappearance of the repressor form of the transcriptional factor Shavenbaby (Svb). Conversely, after placode invagination, artificially prolonging pri expression or constitutive loss of Svb leads to ectopic maintenance of trh expression in noninvaginated placode cells surrounding the properly invaginated domain. These results indicate that the rapid disappearance of pri properly terminates the initial fate induction system and suggest that this termination ensures a smooth transition to the subsequent fate-regulatory program—that is, the maintenance of tracheal cell fate specifically in the invaginated cells. Together, we propose that the transiency of pri serves as a cell-intrinsic molecular timer that controls the transient phase of cell fate induction and ensures the transition between sequential fate-regulatory systems, thereby enabling the precise coordination of cell identity with morphogenesis during organogenesis.